2016
DOI: 10.1111/bjd.14821
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization, inpatient burden and comorbidities associated with bullous pemphigoid in the U.S.A.

Abstract: Hospitalization for BP increased significantly between 2002 and 2012. Moreover, there were significant ethnic and healthcare disparities with respect to hospitalization and inpatient mortality from BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
90
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 14 publications
6
90
2
6
Order By: Relevance
“…The management of both subgroups has been largely based on immunosuppression through corticosteroids and steroid sparing agents, mycophenolate mofetil, azathioprine and cyclophosphamide . Infections, osteoporosis and metabolic derangements are frequently encountered adverse effects secondary to therapy . Numerous advances in our understanding of these diseases have allowed for treatment strategies that go beyond non‐specific immunosuppression .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of both subgroups has been largely based on immunosuppression through corticosteroids and steroid sparing agents, mycophenolate mofetil, azathioprine and cyclophosphamide . Infections, osteoporosis and metabolic derangements are frequently encountered adverse effects secondary to therapy . Numerous advances in our understanding of these diseases have allowed for treatment strategies that go beyond non‐specific immunosuppression .…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Infections, osteoporosis and metabolic derangements are frequently encountered adverse effects secondary to therapy. 16,18,[28][29][30][31][32][33] Numerous advances in our understanding of these diseases have allowed for treatment strategies that go beyond non-specific immunosuppression. 34,35 The application of rituximab and intravenous immunoglobulin (IVIg) in combination has shown how different aspects of these diseases can be effectively targeted.…”
Section: Introductionmentioning
confidence: 99%
“…BP180 is the primary autoantigen of BP, and BP230 is the only target of autoantibodies in approximately 8% of patients with BP . It has been reported that elderly patients with BP sometimes have comorbidities associated with neurological disease, such as dementia . BP antigens and their isoforms can be identified in skin and in neuronal tissues, suggesting that exposure of the neuronal antigen may lead to an immune reaction against the epithelial isoform .…”
mentioning
confidence: 99%
“…1 It has been reported that elderly patients with BP sometimes have comorbidities associated with neurological disease, such as dementia. 2 BP antigens and their isoforms can be identified in skin and in neuronal tissues, suggesting that exposure of the neuronal antigen may lead to an immune reaction against the epithelial isoform. 3 Here, we describe two cases of BP in elderly patients with dementia in which the autoantibodies reacted to BP230 but not to BP180 (BP230type BP).…”
mentioning
confidence: 99%
“…
In this issue of the BJD, Ren and colleagues from Northwestern University in Chicago investigate admission rates in patients with bullous pemphigoid (BP) from a dataset of over 78 million patients admitted to hospitals in the U.S.A., for either a primary or secondary diagnosis of BP. 1 In the decade 2002-2012, hospitalizations for a primary diagnosis of BP increased by 26%, while for a secondary diagnosis of BP they increased by 62%. Why is this?BP is a condition known to be more prevalent in the elderly, but in the 10 years in question, survival rates in the general population have not increased by so much.
…”
mentioning
confidence: 99%